PENAFSIRAN THABATHABA’I DALAM AL-MIZAN FI TAFSIR AL-QUR`AN - Ummu Sa’adah (MAQASHID, 2022)
Tabataba'i interpretation in Tafsir al-Mizan follows the form of bil ra`y interpretation (departing from objective and argumentative rational thinking), with the source of the interpretation of the Qur'an itself and the Prophet's Hadith which is based on Shi'a Imams. The method/system of interpretation used by Tabataba'i is the tahlily (analytical) method with a multidimensional approach with an adaby ijtima'i (social) interpretation style. In addition, Tabatabai is classified as an exegete who uses the modern paradigm of thinking.